Effectiveness of Stress Management with Cognitive-Behavioral Approach on Anxiety Sensitivity of the Mothers with Cancerous Children - Haji Seyed Javadi, Tahere; Hatami, Mohammad; Ahadi, Hassan; Kraskian, Adis (International Clinical Neuroscience Journal, 2017)
Background and Purpose: Cancer is considered as one of the most radical hygienic issues in children. It threats the health and active lives of children and their parents causing numerous personal, familiar and social damages in physical, mental and social dimensions. This study aimed to investigate the effectiveness of stress management with cognitive-behavioral approach on the anxiety sensitivity of the mothers with cancerous children. Methods: In a quasi-experimental with pretest- posttest study, 30 mothers with cancerous children were selected using purposeful sampling and divided into case and control groups. Both groups were given pretest using the 16 questions questionnaire of anxiety sensitivity. Then, the skills of stress management with cognitive-behavioral approach were taught to the case group for 8 sessions and the control group didn’t receive any intervention. Finally both groups were given posttest and the data were analyzed using one-way and single variable variance analysis through SPSS21 software. Results: Mothers in case group showed reduction in the anxiety compared to the control one and it was maintained in the following period (p < 0.01). The highest reduction was in the parameter of the fear of physical concerns (p < 0.01). Conclusion: Teaching the methods of coping with stress with cognitive-behavioral approach is an effective strategy for helping mothers with cancerous children due to its high efficiency especially when it is held in groups.